Studi Analisis Isi: Representasi Kritik Politik dan Ideologi Komunis pada Lukisan Karya Hendra Gunawan - Ivan Kurniawan; Muhammad Lutfi Aris (Universitas Komputer Indonesia, 2021)
This study seeks to explore the political interests and ideology of communism which are considered to be represented in the paintings of Hendra Gunawan by the Orde Baru regime. Using the content analysis method, this study will review the intent that Hendra Gunawan was trying to convey in 10 paintings themed on people's lives from 1950 to 1968, a phase where political party intervention in art is suspected. The results showed that there was a match between the political interests of the communist group and the interpretation of the painting in the form of messages expressed by Hendra in his paintings. By looking at the compatibility between the message conveyed by Hendra in his painting, and the indicators designed based on the Prinsip Kesenian 1959, most of which contain the political interests of the communist group in the cultural realm. So it can be concluded that Hendra Gunawan's painting is a painting that is quite ideal for the interests of the communist group, by fulfilling 4 of 5 aspects, namely ideological aspects, class struggle, cultural values, and practical aspects. However, the non-fulfillment of 1 aspect in the form of describing the ideal conditions of the revolution resulted in the possibility of Hendra's idealism being maintained, a possibility that is also a weakness of this research, in addition to the focus of research which only raises 1 character. Apart from that, it is very important to reveal the facts about Hendra Gunawan, because at that time Hendra with his work was recognized as one of the widely known masters of painting. It is hoped that, even though his paintings contain the ideology of communism, this does not necessarily become the reason for the disappearance of Hendra's figure from history books. Because by eliminating the name Hendra Gunawan, it means you have removed an important part of the Indonesian art heritage. Key Words : representation, politics, communism, paintings, hendra gunawan